Efecto de bacterias rizosféricas en la germinación y crecimiento del pimiento (Capsicum annuum L.) bajo invernadero - Tinoco Gualán, Gabriela Maritza (2024)
The objective of this research was to determine the effect of rhizospheric bacteria on the germination and growth of pepper (Capsicum annuum L.) under a greenhouse. Hybrid seeds of Marcato F1 were used, inoculated with three types of bacteria: Azospirillum sp., Azotobacter sp. and Pseudomonas sp., the experiment had a completely randomized block design with 5 treatments (T1=Azospirillum sp., T2=Azotobacter sp., T3=Pseudomonas sp., T4=NewGibb, T5=Control); and 6 repetitions. Parameters related to germination, vegetative and reproductive development and biomass accumulation were evaluated; In the seedbed it was determined: germination, plant height, stem diameter, root length and in the greenhouse: plant height, leaf area, number of fruits, fruit length and diameter, fresh and dry matter. The best treatment was (Pseudomonas sp.) that improved in most variables of pepper growth and production. Finally, the results obtained in the present study represent sustainable options to totally or partially replace synthetic fertilizers for conventional use as a promising alternative to increase agricultural production in a more sustainable way.